Karakteristik dan Analisis Risiko Kasus Tuberkulosis di Puskesmas Senen Jakarta Pusat tahun 2023 - Susanti, Eka Lusi; Hasnaini, Anna; -, Murniaty (UI Scholars Hub, 2024)
Indonesiaranks second globally with the highest number of Tuberculosis (TB) cases, following India. Consequently, TB remains a high-priority health issue requiring immediate attention. This study aims to describe the TB case characteristic and analyze the TB risk in each urban villages of Senen, Central Jakarta. This is a descriptive cross-sectional study. Data was obtained from medical records and the Tuberculosis Information System (SITB) at Senen Primary Health Care (PHC) during January – December2023. Demographic data, TB type, result of rapid molecular test, and comorbidities were presented in numbers and percentages. Total TB cases, incidence rate (IR), and standardized morbidity ratio (SMR) were calculated for each urban villages and the entire subdistrict. The distribution of the number of cases, IR, and SMR was displayed on a map. Overall, 300 TB cases were found among 3,421 suspected TB cases examined at the Senen PHC in 2023, with a positivity rate of 7.22% and an incidence rate of 240 per 100,000 population. The highest number of TB cases occurred in September 2023 with 52 cases (17.33%). Of the total TB cases in Senen, TB cases were commonly found in males (67.67%), the productive age group (15-59 years) accounted for73.33%,new TB cases accounted for 93.33%, 100% were pulmonary TB cases, 82.33% were bacteriologically confirmed with 93.36% of them being drug-sensitive TB (DS-TB), smokers (73.33%) and employed (72.67%). TB cases were spread across sixurban villages, with Kramat having the highest number of cases at 98 (32.67%), a TB IR of 78 per 100,000 population, and an SMR of 0.71. TB cases occurred throughout the year in the Senen Subdistrict. The characteristics of TB cases in Senen were dominated by males, productive age groups, pulmonary TB, new cases, bacteriologically confirmed cases, DS-TB, smokers, and employed individuals. The TB risk varied in each area, with the highest number of cases, IR, and SMR found in Kramat urban village A comprehensive strategy combining early detection, effective treatment, and preventive measures is essential to control the TB epidemic in the Senen Subdistrict.